The Role of Mothers Knowledge Regarding Nutritional Needs of Toddlers Nutritional Status - Wenny Rahmawati; Dwi Norma Retnaningrum (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
The issue of nutrition is set as an essential point in the Sustainable Development Goals (SDGs). One of the SDGs targets related to nutrition is that by 2030 all forms of malnutrition in children under five must end. The incidence of malnutrition in children under five is strongly influenced by the knowledge of parents. Knowledge of nutrition is an essential provision for mothers to provide balanced nutrition for their toddlers. The purpose of the study was to prove the role of mother's knowledge regarding nutritional needs on nutritional status of children under five in Sukomulyo Village. The research design is correlational analytic approach cross sectional Data was collected on 74 mothers who have toddlers using stratified random sampling technique. The results of the study showed that the mother's knowledge about nutritional needs was mostly (50%) sufficient. Most of the nutritional status of children under five (66.2%) is good.test Spearman rank obtained the rs value of 0.405 and the p value (sig.) = 0.000 < 0.05. Researchers suggest the need for mothers of toddlers to further increase their knowledge about the nutritional needs of toddlers, so that the nutritional status of toddlers can be improved even more and can prevent malnutrition.